Prevalence of hepatic granulomas in chronic hepatitis B - (:unkn) unknown (My University, 2004)
An increasing frequency of hepatic granulomas, up to 10%, in chronic hepatitis C patients is reported, and their presence is considered to be a predictor of treatment success. However, there is only one prevalence study on granuloma in chronic hepatitis B, and its significance for treatment outcome is unknown. We aimed to determine the prevalence of hepatic granulomas in a larger group of chronic hepatitis B patients and to compare their presence with the response to interferon therapy. Biopsy specimens of chronic hepatitis B patients were reevaluated for the presence of hepatic granulomas. All patients with hepatic granuloma were screened for other granulomatous diseases by tuberculin skin test, chest X-ray and computed tomography, venereal disease research laboratory, Brucella agglutination tests, and exposure to hepatotoxic agents. We screened 663 cases of chronic hepatitis B. Hepatic granulomas were found in 10 cases (1.5%). The granulomas could not be ascribed to any other reason. Of the 10 patients with hepatic granulomas, 4 responded to interferon therapy, 2 dropped out, and 4 were nonresponders. We conclude that hepatic granuloma is a rare finding in chronic hepatitis B and its presence does not seem to predict the response to interferon therapy.
Keywords: Adult; Female; Humans; Middle Aged; Prevalence; Male; Antiviral Agents; Hepatitis B, Chronic; Liver Diseases; Granuloma; Interferons